Imaging and Clinical Characteristics of 8 Cases of COVID-19 Complicated with Pneumomediastinum in Children - FU Qiang, REN Zuolei, LIN Zhiqiang, GONG Jianfeng, WANG Changzheng, WANG Ting, HU Yalan, TAN Jufang (Zhongguo quanke yixue)
Background The imaging of COVID-19 (COVID-19) in children is different from that of adults, mainly manifested as subpleural ground glass shadows, patchy high-density shadow, and solid shadow, and rarely complicated with pneumomediastinum. The formation of a large number of emphysema can seriously affect the respiratory and circulatory function, resulting in obvious wheezing and hypoxemia, which need to be actively treated. Objective To analyze and summarize the imaging and clinical characteristics of COVID-19 with pneumomediastinum in children. Methods A retrospective analysis was conducted on 8 pediatric patients with COVID-19 complicated with pneumomediastinum admitted to the Department of Pediatrics at Jingzhou Hospital Affiliated with Yangtze University from December 1, 2022 to January 30, 2023, including age, gender, imaging, clinical characteristics, and treatment. Results 8 children were 3.5 years to 12 years, with a female ratio of 3∶5. High Resolution CT Scan in all children showed double lung infection combined with pneumomediastinum, and multiple emphysema involved the neck and chest wall. The pulmonary manifestations were various: subpleural ground glass shadow, consolidation, tree bud sign, vascular bronchial bundle thickening and bronchial wall thickening, grid sign, etc., no large consolidation and "white lung" found. One case was observed to have a small amount of pleural effusion. In addition to fever and cough, the clinical manifestations were obvious shortness of breath, pulmonary auscultation, but dry or moist rales were not significant. Four children with mycoplasma infection were treated with azithromycin, and one with B. catarrhalis. was treated with azithromycin. All given oxygen therapy. A patient was treated with an invasive ventilator because traditional treatment was unable to alleviate her dyspnea and hypoxemia. The patient's leucocytes and hypersensitive CRP were significantly increased. After 3 days, the symptoms improved and the machine was successfully withdrawn. 5 cases were treated with intravenous immunoglobulin (IVIG), and 3 cases were treated with glucocorticoids. a week after the review of chest CT, pneumomethinum were completely absorbed, and lung lesions significantly improved. Conclusion Children with pneumomediastinum complicated by COVID-19 were mostly pre-school or school-age children, rare in infants. Pneumomediastinum can coexist with gas accumulation in the neck and chest wall. In addition, pulmonary lesions could involve the stroma or parenchyma, and both lungs were affected, with various manifestations. At the onset of the disease, there were obvious shortness of breath, active oxygen therapy was recommended. When the white blood cell count and hypersensitivity CRP significantly increase, close attention should be paid to respiratory conditions. IVIG and glucocorticoids may have positive effects, and if necessary, a mechanical ventilation should also be used.